The Influence of Group Guidance on Student Learning Attitudes - Cetrisnawati Cetrisnawati; Ardimen Ardimen; Dasril Dasril; Nursyamsi Nursyamsi (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
This research aims to evaluate the positive impact of group guidance using a muhasabah approach on improving students' learning attitudes. A strong learning attitude is considered crucial for individual success, and a lack of a good learning attitude can be a hindrance to achieving academic accomplishments. In this context, the study focuses on students identified with low learning attitudes. The research methodology employed is quantitative with a one-group pre-test-post-test experimental design. The sample consists of 15 students selected randomly using simple random sampling. Data collection is conducted through non-test techniques using a Likert scale to measure students' learning attitudes. The results indicate that group guidance with a muhasabah approach has a significant influence on enhancing students' learning attitudes. These findings contribute to our understanding of the effectiveness of this method as a strategy to boost motivation and improve students' learning attitudes in the pursuit of academic success.